The relation between short-term memory and vocabulary skills in Greek children with cochlear implants: The role of hearing experience. Issue 4 (August 2018) - Talli, Ioanna; Tsalighopoulos, Miltiadis; Okalidou, Areti
Weak performance in short-term memory (STM) in children with cochlear implants (CI) may have an impact on vocabulary development. Vocabulary, phonological STM (non-word repetition), phonological/verbal STM (digit span) and rapid naming measures were administered to 15 Greek-speaking children with CI (ages 4;6–8;6) and to chronological age (CA) and younger controls with normal hearing (NH). The children with CI exhibited lower performance in all tasks compared to CA controls but lagged behind only in phonological STM tasks in comparison to younger NH controls. For children with CI, vocabulary correlated with phonological STM, while for younger NH controls it correlated with all the cognitive measures used. The present results showed that children with CI demonstrate age-matched rapid naming skills, a slower development in vocabulary acquisition rates and developmental lags in their phonological STM skills, suggesting an overall atypical pattern of development. The results also suggest a relationship between these skills which needs to be explored further.